“You take care of people, people will take care of you”: Moral Economies and an Unpredictable Drug Market - Erin E. Gould; Siddhi S. Ganesh; Anthony J. DiMario; Jimi Huh; Ricky N. Bluthenthal; Rachel Carmen Ceasar (PLoS ONE, 2025)
Introduction Fentanyl is the leading cause of opioid-related overdose deaths in the United States. Given the exogenous market shock of fentanyl and subsequent transition in the illicit opioid supply, our analysis sought to explore the social and relational experiences of people who use opioids (PWUO). Methods We conducted qualitative interviews with 30 PWUO (n = 30) in Los Angeles, CA from July 2021 to April 2022. To be eligible for this study, participants had to report being 18 years of age or older and any self-reported opioid, cannabis, and injection drug use within the past 30 days. We used constructivist grounded theory to analyze the contexts that contribute to lived experiences surrounding opioid use behaviors within social networks. Results Within an unpredictable drug market contaminated by fentanyl, participants reported: 1) avoiding opioid withdrawal symptoms by sharing financial and material resources within social networks, 2) securing and cultivating known, predictable social ties to prioritize safe/ safer supply of opioids, and 3) avoiding and mitigating risk of overdose fatality by using opioids within peer groups. Conclusions Our findings emphasize that while peer support plays a critical role in safety within moral economies of PWUO, structural changes are needed to address the additional harms from an unregulated drug supply. Harm reduction interventions such as fentanyl test strip and naloxone distribution, as well as medication for opioid use disorders may improve safety. However, with a fentanyl-contaminated drug supply increasing risk for PWUO, safer opioid distribution of pharmaceutical-grade opioids and overdose prevention programs are needed to effectively address the burden of withdrawal, overdose, and fatality prevention within peer groups.